Physics education research over the last two decades: a bibliometri̇c analysis - SÜZÜK, EROL (My University, 2023)
Physics is a crucial subject for secondary school students' scientific literacy and future participation in STEM-related disciplines. It is essential for teaching physics and providing students with fundamental knowledge and skills. Physics education research (PER) aims to understand how students learn physics and improve physics instruction. PER is a multidisciplinary field that integrates perspectives from physics, education, philosophy, history of science, and cognitive psychology. PER in Turkey focuses on multiple facets of physics education, with recent studies examining how students learn advanced physics concepts. Bibliometric analysis is a research methodology that utilizes quantitative and mathematical data to scrutinize patterns within a specific scientific domain. It helps identify research gaps and emphasize areas for future research. Bibliometric analysis has been used to analyze publications in the field, identify research gaps, and emphasize areas for future research. This study aimed to understand the subjects of articles published in the Web of Science database over the past two decades by analyzing bibliometric data. This study analyzes physics education research globally and in Turkey, revealing that journal articles are the most prevalent document in the field. The study identifies 2020 as the year with the highest number of physics education publications worldwide, with Turkey making significant contributions in 2012 and 2014. However, there are differences between global and Turkish studies, with fewer references to Vygotskian perspective, physics identity, and NOS. In addition, it has been determined that important issues such as equality and gender inequality do not receive much attention in Turkish studies. Turkey's research community is second only to American researchers in terms of productivity, indicating an effective community of physic education researchers. The absence of equity focus in Turkish physics education studies could be due to structural problems like inadequate laboratory facilities and crowded classrooms. Researchers should focus on equity issues and address systemic problems to ensure equitable physics education for all students. International collaboration among researchers from diverse countries is recommended to enhance perspectives and stimulate innovative approaches in the field.
Keywords: Physics education; bibliometric analysis; VOSviewer